Rapid and specific on-site H5Nx avian influenza diagnosis via RPA and PAM-independent CRISPR-Cas12a assay combined with anti-NP antibody-based viral RNA purification - Song, Jin-Ha; Son, Seung-Eun; Kim, Ho-Won; Kim, Seung-Ji; An, Se-Hee; Lee, Chung-Young; Kwon, Hyuk-Joon; Choi, Kang-Seuk (Frontiers in Veterinary Science, 2025)
Rapid and accurate detection of H5Nx avian influenza viruses is critical for effective surveillance and control measures. Currently, RT-qPCR with spin column RNA extraction is the gold standard for HPAIV surveillance, but its long reaction time and need for specialized equipment limit its effectiveness for rapid response. In this study, we introduce a centrifuge-free, rapid detection method for on-site detection of H5Nx viruses that combines magnetic bead-based ribonucleoprotein (RNP) purification and concentration with a CRISPR-Cas12a system that is independent of the protospacer adjacent motif (PAM) sequence. Our approach employs anti-NP monoclonal antibodies for the targeted isolation of RNA bound to RNPs, facilitating a quick and specific RNA extraction process that negates the need for centrifugation. Additionally, by denaturing the RT-RPA amplicon using 60% DMSO, we activate the trans-ssDNA cleavage activity of the Cas12a protein without the need for a specific PAM (5’-TTTV-3′) sequence. This strategy increases flexibility in CRISPR RNA design, providing a significant advantage when targeting genes with high variability. We validated the efficacy of our magnetic RNP purification and concentration method in combined with an RT-RPA/PAM-independent Cas12a assay for detecting the H5 gene. The assay achieved a sensitivity threshold of 101 EID50 with fluorescent detection and 102 EID50 using lateral flow strips. It also exhibited high specificity, yielding positive results solely for H5Nx viruses among various influenza A virus subtypes. Furthermore, in clinical samples, the assay demonstrated 80% sensitivity and 100% specificity. These results highlight the advantages of using NP-specific antibodies for RNP purification and CRISPR-Cas12a with viral gene-specific crRNA to achieve exceptional diagnostic specificity.